OFD1 Is Mutated in X-Linked Joubert Syndrome and Interacts with LCA5-Encoded Lebercilin - Coene, Karlien L.M.; Roepman, Ronald; Doherty, Dan; Afroze, Bushra; Kroes, Hester Y.; Letteboer, Stef J.F.; Ngu, Lock H.; Budny, Bartlomiej; van Wijk, Erwin; Gorden, Nicholas T.; Azhimi, Malika; Thauvin-Robinet, Christel; et al. (American journal of human genetics, 2009)
We ascertained a multi-generation Malaysian family with Joubert syndrome (JS). The presence of asymptomatic obligate carrier females suggested an X-linked recessive inheritance pattern. Affected males presented with mental retardation accompanied by postaxial polydactyly and retinitis pigmentosa. Brain MRIs showed the presence of a “molar tooth sign,” which classifies this syndrome as classic JS with retinal involvement. Linkage analysis showed linkage to Xpter-Xp22.2 and a maximum LOD score of 2.06 for marker DXS8022. Mutation analysis revealed a frameshift mutation, p.K948NfsX8, in exon 21 of OFD1. In an isolated male with JS, a second frameshift mutation, p.E923KfsX3, in the same exon was identified. OFD1 has previously been associated with oral-facial-digital type 1 (OFD1) syndrome, a male-lethal X-linked dominant condition, and with X-linked recessive Simpson-Golabi-Behmel syndrome type 2 (SGBS2). In a yeast two-hybrid screen of a retinal cDNA library, we identified OFD1 as an interacting partner of the LCA5-encoded ciliary protein lebercilin. We show that X-linked recessive mutations in OFD1 reduce, but do not eliminate, the interaction with lebercilin, whereas X-linked dominant OFD1 mutations completely abolish binding to lebercilin. In addition, recessive mutations in OFD1 did not affect the pericentriolar localization of the recombinant protein in hTERT-RPE1 cells, whereas this localization was lost for dominant mutations. These findings offer a molecular explanation for the phenotypic spectrum observed for OFD1 mutations; this spectrum now includes OFD1 syndrome, SGBS2, and JS.